Post-traumatic spatial self-organization of mobile populations (Transactions of the Association of European Schools of Planning, 2020)
Since 2012, and particularly since 2014, instability and wars in North African countries and the Middle East have brought a wave of refugees, trying to flee from violence in their countries, to Europe. They usually go north, crossing the Mediterranean towards Italy, or the Aegean, going west to the Greek islands. In their quest for a safe refuge, a significant number drown or disappear. The rest reach in Europe carrying their traumatic experiences with them, and face immediate humanitarian needs. A major task for host cities is to provide shelter for the refugees, taking into consideration the influence of their psychological trauma on local societies. This complex task, which combines technical, economic, social, psychological, and political dimensions – simultaneously targeted on two social groups – constitutes the ‘post-traumatic urbanism’ which intervenes in the recreating of the refugees’ spatial and social networks in the host city. This paper discusses how the complex issue of post-traumatic housing triggers spatial self-organization by the refugees, in contrast to the ‘official’ provisions from host states, through the lens of complex adaptive theory (resilience). This article examines the features of refugee housing in Athens and Thessaloniki through qualitative research, quantitative methods and participatory observation. Through this study, it is highlighted that the post-trauma self-organization of mobile populations is a process of gaining dignity and self-respect in a new and often hostile environment, and a tool for spatial and social resilience.
Keywords: Refugee; post trauma; self-organization; host city